ISLAMIC GOVERNANCE IN ISLAMIC SCHOOL FINANCE - Ahmad Munir Hamid (Center of Language and Cultural Studies, 2018)
The purpose of this study is to analyze the concept of Islamic finance governance which includes the principles among others; tauhid, taqwa and ridho, equilibrium (balance and justice), benefit, transparency, responsibility (responsibility) and independence. This research uses descriptive qualitative method using literature approach (literature), either in the form of books, notes, or research result report, from previous researcher. The literature used in this research is books, journals, theses, and articles related to Good Corporate Governance in Islamic perspective and its application to sharia banking in the world.Islam has a much more complete and more comprehensive concept and akhlaqulkarimah and ketaqwaan to Allah SWT is a solid wall not to get mired in illegal practices and dishonest in accepting the mandate. Principles of Islamic Governance (IG) after going through the process of analysis and data processing there are nine interrelated principles, the principles are derived kalamullah and rasulullah who can answer from some corruption crime to efforts in improving efficiency, competitiveness and product innovation and sharia banking services.